Neutralisation of virulence activity of enterohemorrhagic Escherichia coli O157:H7 in vitro through hyperimmune bovine colostrum - Girón, Daniel; Marques Da Silva, Wanderson; Vilte, Daniel Alejandro; Smith, Libia Yael; Casabonne, Maria Carolina; Maldonado May, Veronica; Cataldi, Angel Adrian; Ibarra, Cristina Adriana; Larzabal, Mariano; Sacerdoti, Flavia (Wiley, 2025)
Background, Context or Rationale Enterohemorrhagic Escherichia coli (EHEC) O157:H7 infection in humans may cause bloody diarrhoea, haemorrhagic colitis and haemolytic uremic syndrome (HUS). Cattle are the main reservoir of EHEC and a source of infection for humans. It has been previously demonstrated that hyperimmune bovine colostrum (HC) against virulence factors of EHEC was efficiently transferred to newborn calves through lactation. Also, it is well described that human consumption of HC can provide therapeutic effects on several gastrointestinal infections.